The Resource-Based View and Dynamic Capabilities: Considering Competitive Advantage in the Gallagher Rugby Premiership - Smith, Matthew Lloyd (2020)
The Resource-Based View of the firm is a well known fixture of strategic management theory. However, the theory is often criticised as not being applicable in dynamic environments as its logic cannot explain how an organisation gains competitive advantage. Dynamic Capabilities theory, to a large extent, grew out of the criticisms revolving around the Resource-Based View. Here the Resource-Based View and Dynamic Capabilities theory are explored through the use of three case studies taken from a dynamic environment: sport. Specifically, this work looks at the cases of Gallagher Premiership men’s rugby union teams Bristol Bears, Saracens, and Leicester Tigers. This will be done through the use of secondary data, to address three research questions. A literature review, covering the Resource-Based View of the firm and Dynamic Capabilities theory will be carried out to examine the theories applicability. A small number of resources from the case studies will then be used as examples to explore the theories and provide practical implications for men’s rugby union. RBV, while lacking explanatory power in terms of competitive advantage in dynamic environments remains a useful tool when considering resources in said environment. Dynamic Capabilities theory provides the explanatory power needed to comprehensively consider competitive advantage in dynamic environments.